Clinical presentation, management and outcomes of differentiated thyroid cancer: a tertiary center experience - Samer Ahmed Ibrahim; Ahmed Adly Mohammed; Mohammed Naguib Mohamed; Reham Mohamed Faheim; Rehab Saeed Hussein; Ahmed Abdelmoneim Teaima (The Egyptian Journal of Otolaryngology, 2026)
Abstract Introduction Thyroid cancer is considered the most common endocrine tumor worldwide and its incidence is increasing. Objective We conducted this study to analyses demographic, clinicopathological, imaging data, treatment, outcomes, recurrence rate, overall survival and prognosis of differentiated thyroid cancer (DTC) cases. Patients & methods This is a retrospective study done in our tertiary hospital including patients diagnosed with DTC from 2015 to 2020. One hundred seventy-six patients’ data were reviewed including full detailed history, thyroid and lymph node assessment, radiology results, preoperative staging, surgical modalities, histopathological diagnosis, postoperative risk stratification, radioactive iodine ablation therapy and outcomes including recurrence, overall survival, disease free survival. Results Mean age of the studied patients was 42.74 ± 12.19 years old. Most of the studied patients were females representing 84.1% meanwhile males represented 15.9%. There were 147 in stage I (83.5%), 22 in stage II (12.5%), 5 patients in stage III (2.8%) and 2 in stage IV (1.1%). Near half of the studied patients underwent neck dissection. Most of the studied patients received postoperative radioactive iodine (RAI). 9.1% of the treated patients had nodal recurrence. Patients with recurrence were significantly older than non-recurrence patients. Recurrence is significantly more in old and male patients and with positive lymph nodes involvement. Most of the pathological parameters were not significantly related to recurrence with exception of capsular invasion which showed significant correlation with recurrence. 5-year survival was 95.9%. 5 years disease free survival was 85.1%. Conclusion Patient age, lymph node metastases, capsular invasion, and tumor size were the most important prognostic factors in relation to recurrence rate, while the roles of tumor multifocality and lymphovascular invasion were insignificant.